Control of product nature and morphology by adjusting the hydrogen content in a continuous chemical vapor deposition process for carbon nanotube synthesis. (October 2016) - Ma, Yang; Dichiara, Anthony B.; He, Delong; Zimmer, Laurent; Bai, Jinbo
Abstract: Floating catalyst chemical vapor deposition (FCCVD) is commonly considered as one of the most attractive processes for the production of carbon nanotubes (CNTs). Understanding the phenomena occurring during the FCCVD synthesis of CNTs is critical to improve the process selectivity and scalability. The present work correlates information on gas chemistry and structural characteristics of the carbonaceous products, and show how both are strongly related to the hydrogen content in the reactor. Hydrogen plays different roles in the CNT growth process whose contributions depend on the synthesis conditions. Its presence induces an augmentation in carbon supply by promoting the decomposition of hydrocarbon vapors into more reactive byproducts, and by serving as an activation agent for the dissociation of physisorbed hydrocarbons on the surface of catalyst particles. However, high hydrogen content can induce catalytic hydrogenation of carbon and lead to surface modification of CNTs. Hydrogen also interferes with the decomposition of catalytic precursors, thus influencing the size and availability of catalyst nanoparticles. As a result, the mean and core diameters, crystallinity of the graphene walls, and length of CNTs are greatly influenced by the hydrogen flow, which offers the possibility to tune the CNT properties in a very simple, yet efficient way.